MEMBANGUN JARINGAN TEMA DALAM PEMBELAJARAN TEMATIK: KRITERIA, PRINSIP DAN LANGKAH PENGEMBANGANNYA - Hasanah, Kartini Dwi; Derajat, Lingga Saniman; Susilawati, Samsul (Ibtida'iy : Jurnal Prodi PGMI, 2024)
Thematic learning is an approach that integrates various scientific disciplines through themes that are relevant to students' daily lives, aiming to increase their understanding and involvement in the learning process. The aim of this research is to review in depth the criteria, principles and techniques for developing theme networks in thematic learning, including the steps that must be taken to create effective and interesting themes as well as highlighting the advantages and disadvantages of thematic learning models based on theme networks. This research uses quantitative methods with a library research approach to explore theme networks in thematic learning. This research focuses on collecting data from various literature sources, including books, scientific journals, government documents, and relevant online articles. The results of this research are: (1) criteria and techniques for systematic steps in developing a theme network which is the basis for integrated learning. (2) An effective theme network must pay attention to principles such as simplicity, cohesiveness, and relevance to the student context. (3) choosing the right theme and good time planning is very important for the successful implementation of thematic learning.